Truth, Politics, and Universal Human Rights - Madigan, J.; SpringerLink (Online service) (New York : Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2007)
This book uses the concept of universal human rights to explore the relationship between the individual, society, and truth. To answer the question of how we say something universally true about human beings while lacking the philosophical means to do so, the author explores the changing relationship between truth and politics from Plato to Locke.
Keywords: Political theory; Political philosophy; Social justice; Human rights; Political science; World politics; Political Theory; Political Philosophy; Social Justice, Equality and Human Rights; Political Science; Human Rights; Political History